Analisa Penerapan Teknologi UMTS Untuk Mengatasi Permasalahan Kapasitas Pada Jaringan 2G (GSM) - Alfin Hikmaturokhman; Wahyu Pamungkas; Luthfiana Luthfiana (JURNAL INFOTEL, 2012)
A high necesarry data service and bigger network capacity becomes a critical issue in the GSM network. One of the good and bad size parameter reference-quality GSM network can be viewed on the performance parameters MLSLOT Allocation Blocking. The default value for parameter MLSLOT Allocation Blocking are ? 40 % that the network is otherwise well. To overcome these problems it is applied to UMTS technology. The study was conducted to determine how the performance of the 2G PT Indosat Tbk. Before and after the application of technology and how it compares to the performance of UMTS cellular network PT Indosat Tbk. before and after implementation of a UMTS network. In conducting this study the authors to collect the necessary data and did the interview if the supervisor does not know From the research the average value MLSlot Bocking Allocation has decreased, for the first sector decreased on average uplink 0.70% to 0.17% down 0.53%.The average downlink 26.49% to 14.98% down 11.51%. Sector 2 uplink average 0.24% to 0.00% down 0.24%, the average downlink 5.16% to 0.04% down 5.12%, Sector 3 uplink average 0.6% to 0.21% down 0.39%, the average downlink 23.99% to14.98% down 9.01%.